2020
DOI: 10.1002/vms3.246
|View full text |Cite
|
Sign up to set email alerts
|

First report of a canine morbillivirus infection in a giant anteater (Myrmecophaga tridactyla) in Brazil

Abstract: Canine morbillivirus, also known as canine distemper virus (CDV), induces a contagious multisystemic disease caused by an enveloped RNA virus belonging to the genus Morbillivirus within the family Paramyxoviridae . CDV replicates readily in epithelial, nerve and lymphoid tissues; it is excreted in urine, feces, saliva, oral and nasal discharge; and its major route of entry for infection is through the respiratory system. Although the virus was originally believed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…CDV is a highly contagious virus that can cause fatality in the domestic dog [3,4]. The distemper virus affects a wide range of animal families, both domestic and wild, including Canidae (dog, fox, wolf, raccoon dog), Mustelidae (ferret, mink, skunk, wolverine, martin, badger, otter), Procyonidae (raccoon, coati), Ailuridae (red panda, giant panda), Ursidae (bear), Elephantidae (Asian elephant), some primates (Japanese monkey), Viverridae (civet), Pinnipedia (seals, walrus, sea lion), Felidae (large cats), Myrmecophagidae (Tamandua tetradactyla) commonly known as Southern tamandua, and most recently reported in giant anteater (Myrmecophaga tridactyla) in Brazil [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…CDV is a highly contagious virus that can cause fatality in the domestic dog [3,4]. The distemper virus affects a wide range of animal families, both domestic and wild, including Canidae (dog, fox, wolf, raccoon dog), Mustelidae (ferret, mink, skunk, wolverine, martin, badger, otter), Procyonidae (raccoon, coati), Ailuridae (red panda, giant panda), Ursidae (bear), Elephantidae (Asian elephant), some primates (Japanese monkey), Viverridae (civet), Pinnipedia (seals, walrus, sea lion), Felidae (large cats), Myrmecophagidae (Tamandua tetradactyla) commonly known as Southern tamandua, and most recently reported in giant anteater (Myrmecophaga tridactyla) in Brazil [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…CDV is estimated to be present in most countries, and primarily infects Canid species. The virus also infects other animal species belonging to the order Carnivora (including Felidae, Mustelidae, Procyonidae, Ursidae, Phocidae, Viverridae, Hyaenidae, Ailuridae, Mephitidae, and Otariidae) and other orders (Artiodactyla, Primates, Rodentia, and Pilosa) 42–48 . However, studies on CDV infection in wild animals living in endemic areas have shown differences in mortality rates and possession of anti‐CDV antibodies among closely related species 49,50 .…”
Section: Epidemiology Of Current Morbillivirus Speciesmentioning
confidence: 99%
“…The virus also infects other animal species belonging to the order Carnivora (including Felidae, Mustelidae, Procyonidae, Ursidae, Phocidae, Viverridae, Hyaenidae, Ailuridae, Mephitidae, and Otariidae) and other orders (Artiodactyla, Primates, Rodentia, and Pilosa). [42][43][44][45][46][47][48] However, studies on CDV infection in wild animals living in endemic areas have shown differences in mortality rates and possession of anti-CDV antibodies among closely related species. 49,50 While CDV infection is well known to be expanding among wild carnivores, 51,52 a recent study indicated that CDV may also be circulating with wild animals other than dogs as the primary source of infection.…”
Section: Canine Morbillivirusmentioning
confidence: 99%
“…CDV is the causative agent of canine distemper (CD), an acute, highly severe, contagious, and systemic disease that affects carnivores and other wildlife worldwide [ 2 , 9 , 10 , 11 ]. CD is readily transmitted through susceptible hosts via direct contact with oral, respiratory, and ocular fluids, and/or exudates.…”
Section: Introductionmentioning
confidence: 99%